George Haley, Vicente Espinel and Marcos de Obregón. A life and its literary representation. Brown University Press, Providence, Rhode Island, 1959; 254 pp. (Brown University Studies, 25). - A. Zamora Vicente (Nueva Revista de Filología Hispánica, 1959)
Se reseñó el libro: Vicente Espinel and Marcos de Obregón. A life and its literary representation.